Summary Statements in the Gospel of Matthew - Herok, Piotr (The Biblical Annals, 2023)
This article examines the summary statements in the first gospel. The investigation aims to establish a precise set of Matthean texts belonging to this literary genre. Following a presentation of a variety of solutions (R. Schnackenburg, J. Gnilka, E. Schweizer, D.A. Hagner, R.H. Gundry, J. Nolland, A. Paciorek, U. Luz, R.T. France, W.D. Davies and D.C. Allison, C.S. Keener, G.R. Osborne, C.A. Evans, S. Grasso, W. Egger, B. Gerhardsson, L. Novakovic), literary considerations are examined against the background of various scholarly propositions, giving precise criteria to denote a given gospel text as a summary. On this basis, eight Matthean texts are proposed as summaries – (1) 4:23–25, (2) 8:16–17, (3) 9:35–36, (4) 12:15–21, (5) 14:13–14, (6) 14:34–36, (7) 15:29–31, and (8) 19:1–2 – while showing their thematic interpenetration and mutual dependence.